2002
DOI: 10.1007/s00210-002-0533-2
|View full text |Cite
|
Sign up to set email alerts
|

Rewarding effects of ethanol and cocaine in µ opioid receptor-deficient mice

Abstract: To investigate the role of mu opioid receptors in the reinforcing effects of psychotropic drugs, the voluntary ethanol intake and ethanol- and cocaine-induced conditioned place preference in mu opioid receptor-deficient mice and their wild-type counterpartners was tested. Moreover, dopamine D1 and D2 receptor binding was measured. It was found that ethanol intake was significantly lower in deficient mice. Conditioned place preference in wild-type animals was induced with 5.0 mg/kg cocaine and this dose was ine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
92
1
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(97 citation statements)
references
References 59 publications
(62 reference statements)
3
92
1
1
Order By: Relevance
“…Cocaine-induced locomotor activity has not been described previously for chronic NTX pretreated animals. With respect to m-opioid receptor knockout mice, the present findings are in agreement with those of Becker et al (2002) who also reported comparable cocaine-induced locomotor activity for m-opioid receptor knockout mice, which lack exons 2 þ 3 of the m-opioid receptor gene, and wild-type controls. Taken together, mopioid receptors are not required for the acute locomotor response to cocaine in mice.…”
Section: Acute Cocaine-induced Locomotor Activitysupporting
confidence: 92%
“…Cocaine-induced locomotor activity has not been described previously for chronic NTX pretreated animals. With respect to m-opioid receptor knockout mice, the present findings are in agreement with those of Becker et al (2002) who also reported comparable cocaine-induced locomotor activity for m-opioid receptor knockout mice, which lack exons 2 þ 3 of the m-opioid receptor gene, and wild-type controls. Taken together, mopioid receptors are not required for the acute locomotor response to cocaine in mice.…”
Section: Acute Cocaine-induced Locomotor Activitysupporting
confidence: 92%
“…Similarly, m-OR knockout mice self-administer alcohol at lower levels when compared with wild-type controls (Becker et al, 2002;Hall et al, 2001;Roberts et al, 2000). In rodents, chronic alcohol consumption has been shown to increase m-OR binding in limbic areas including the nucleus accumbens (Cowen et al, 1998(Cowen et al, , 1999Djouma and Lawrence, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Targeted gene mutation (knockout) strategies provided mice that lack opioid peptides or receptors. Thus, mice lacking μ-opioid receptors, generated from three distinct constructs, do not self-administer ethanol under various conditions, including oral self-administration and two-bottle choice, and do not display conditioned place preference to ethanol (Becker et al, 2002;Hall et al, 2001;Roberts et al, 2000). Surprisingly, significantly reduced ethanol consumption was also shown in mice lacking κ-opioid receptors (Kovacs et al, 2005).…”
Section: Introductionmentioning
confidence: 99%